*Análisis contrastivo e interlingüístico de peticiones en inglés y español - Tello Rueda, Leyla Yined (Íkala, Revista de Lenguaje y Cultura, 2006)
This article presents the main results of a descriptive investigation in the field of interlanguage pragmatics. It contrasts the requests formed by native speakers of Spanish, by native speakers of English, and by learners of English as a foreign language. Data was collected through a closed role-play, in order to analyze the semantic strategies and the internal and external modifications used by participants in the oral production of requests. This analysis allowed the detection of pragmatic transfer from Spanish to English. This outcome is crucial for the design of methodological and curricular proposals that contribute to offset the effect of this factor as a generator of communicative breakdowns and misunderstandings when learning a second or foreign language. Reçu: 09-03-06 / Accepté: 18-07-06 How to reference this article: Tello Rueda, L. Y. (2006). Análisis contrastivo e interlingüístico de peticiones en inglés y español. Íkala. 11 (1), pp. 89 – 116